CGIAR Gender and Agriculture Research Network annual meeting summary report, 1-4 November 2016 - Orentlicher, Natalie (CGIAR Gender and Agriculture Research Network, 2016)
Science-based innovation is at the heart of CGIAR’s vision of its impact on poverty reduction, food security and climate-smart resource management. Impactful innovation needs to be socially inclusive and gender-equitable. Therefore CGIAR Research Programs (CRPs) aim at improving the gender-responsiveness or transformative effects of CGIAR innovation. The CGIAR Gender and Agriculture Research Network was established to enable CGIAR global research programs (CRPs) to work together in a community of practice that would enhance synergies across programs in gender research. Knowledge-sharing in this community of practice includes the willingness to deepen understanding of how gender disparities and gender relations affect agricultural innovation and to include gender perspectives in technical research. The network members meet once every year to share experience and to address strategic and timely topics. Starting in 2017, the Network will be embedded in a gender platform to be hosted by the CRP on Policy, Institutions and Markets (PIM). CRPs will launch their second phases in 2017. Expectations are high that CRPs will demonstrate the effectiveness of gender research conducted in Phase I by showcasing measurable benefits delivered to women as well as men in their main target areas.